An assessment of students' response toward the use of video as a teaching tool in a Malaysian economy class / Azniza Ahmad Zaini, Roslilee Ab Halim and Zulkifli Ab Ghani Hilmi - Ahmad Zaini, Azniza; Ab Halim, Roslilee; Hilmi, Zulkifli Ab Ghani (2010)
This study was aimed at how students of a Malaysian Economy class would respond to the use of video in the classroom. The course requires students to be aware and knowledgeable of the Malaysian economy development, both before and after independence, and current national economic issues. It is a challenge for students to understand and imagine the country's economic scenario and at the same time relating it to global economic issues. For this reason, a more creative and innovative way in teaching this course was adopted to facilitate student learning, stimulate their interest and attention during lectures and keep them informed of current economic issues. Apart from the conventional method of reading textbooks, lecture notes and power-point presentations, videos that were related to the topics in the syllabus were shown to the students during classes. At the end of the semester, the students were asked to rate how the videos were beneficial to them. The study indicated that generally, the students responded favourably to the use of video in facilitating their learning.